1998
DOI: 10.1108/eum0000000006765
|View full text |Cite
|
Sign up to set email alerts
|

Management development in SMEs: what needs to be done?

Abstract: This paper examines the state of play regarding management development in SMEs. Additionally, it discusses government initiatives which seek to develop SME competitiveness through encouraging increased take‐up of management development. Helping SMEs to develop and grow is important to the national economy and a number of government initiatives are now in place to meet this need. Developing people in line with business objectives is a priority which the government is promoting through the Investors in People pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…This suggests that more established SMEs may have lost their agility to adapt to market trends and to competitors’ strategies and that they may not have the capabilities to make the best of implementing CSR activities. Interestingly, studies have found that “a company's attitude to growth…as well as the structure, skills and age profile of management…dominates its ability to grow” (Smith and Whitaker , p. 179). It is also reported that particular routes to growth may act as a barrier with firms characterized as small and young most likely having to grow organically, in contrast to older, more mature business, most likely to grow through acquisition (Delmar and Davidsson ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that more established SMEs may have lost their agility to adapt to market trends and to competitors’ strategies and that they may not have the capabilities to make the best of implementing CSR activities. Interestingly, studies have found that “a company's attitude to growth…as well as the structure, skills and age profile of management…dominates its ability to grow” (Smith and Whitaker , p. 179). It is also reported that particular routes to growth may act as a barrier with firms characterized as small and young most likely having to grow organically, in contrast to older, more mature business, most likely to grow through acquisition (Delmar and Davidsson ).…”
Section: Resultsmentioning
confidence: 99%
“…Age captures the number of years since the company was established and accounts for the extent to which companies have developed in‐built capabilities to manage effectively their resources and thus achieve high growth. Studies show that while initially age may improve firm growth, in time, older companies tend to grow slower than younger ones, as a result of lack of flexibility and agility (Smith and Whitaker ).…”
Section: Methodsmentioning
confidence: 99%
“…Bishop (), Deakins et al . () and Smith and Whittaker (), for example, found that they place less value on formal practices. They may also lack an awareness of the value that formal HRD practices can offer to an SME (Walker et al ., ).…”
Section: Discussion Of Future Directionsmentioning
confidence: 97%
“…This is despite owner-managers recognising the importance of developing and maintaining management skills (Loan-Clarke et al, 1999;Smith & Whittaker, 1996).…”
Section: Introductionmentioning
confidence: 99%